Plot Analysis of Poe’s “The Tell-Tale Heart” - Putri, Putu Evitya Tundari; Malini , Ni Luh Nyoman Seri (Journal of Language and Applied Linguistics, 2024)
This research is a plot analysis of "The Tell-Tale Heart" by Poe. This research purpose is to analyze the types of plots and analyze the plot structure in "The Tell-Tale Heart" short story. Research data is extracted from Edgar Allan Poe's short story "The Tell-Tale Heart". The method used in data collection is the qualitative method. This study also used theories proposed by Kenney. "The Tell-Tale Heart" is taken because the event in the story begins with the event in the present time, to the next event which is a flashback that supports the first event. Then, proceed back again from the flash-back to the present time. The plot structure has some parts, namely: 1. beginning, 2. middle, 3. end. The beginning of a story is an initial stage that shows the characters in the story, the setting of time and places as well as what the story is about. The middle part contains conflict, complications, and climax.